Minimization of maintenance immunosuppressive therapy after renal transplantation comparing cyclosporine A/azathioprine or cyclosporine A/mycophenolate mofetil bitherapy to cyclosporine A monotherapy: a 10‐year postrandomization follow‐up study. (5th January 2016) - Thierry, Antoine; Lemeur, Yann; Ecotière, Laure; Abou‐Ayache, Ramzi; Etienne, Isabelle; Laurent, Charlotte; Vuiblet, Vincent; Colosio, Charlotte; Bouvier, Nicolas; Aldigier, Jean‐Claude; Rerolle, Jean‐Philippe; Javaugue, Vincent; et al.
Summary: Long‐term outcomes in renal transplant recipients withdrawn from steroid and submitted to further minimization of immunosuppressive regimen after 1 year are lacking. In this multicenter study, 204 low immunological risk kidney transplant recipients were randomized 14.2 ± 3.7 months post‐transplantation to receive either cyclosporine A (CsA) + azathioprine (AZA; n  = 53), CsA + mycophenolate mofetil (MMF; n  = 53), or CsA monotherapy ( n  = 98). At 3 years postrandomization, the occurrence of biopsy for graft dysfunction was similar in bitherapy and monotherapy groups (21/106 vs. 26/98; P  = 0.25). At 10 years postrandomization, patients' survival was 100%, 94.2%, and 95.8% ( P  = 0.25), and death‐censored graft survival was 94.9%, 94.7%, and 95.2% ( P  = 0.34) in AZA, MMF, and CsA groups, respectively. Mean estimated glomerular filtration rate was 70.4 ± 31.1, 60.1 ± 22.2, and 60.1 ± 19.0 ml/min/1.73 m 2, respectively ( P  = 0.16). The incidence of biopsy‐proven acute rejection was 1.4%/year in the whole cohort. None of the patients developed polyomavirus‐associated nephropathy. The main cause of graft loss ( n  = 12) was chronic antibody‐mediated rejection ( n  = 6). De novo donor‐specific antibodies were detected in 13% of AZA‐, 21% of MMF‐, and 14% of CsA‐treated patients ( P  = 0.29). CsA monotherapy after 1 year is safe and associated with prolonged graft survival in well‐selected renal transplant recipient (ClinicalTrials.gov number: 980654).